An innovative second-order design method for the structural optimization of the SpiderFLOAT offshore wind Platform. (15th May 2021) - Damiani, Rick; Franchi, Max
Abstract: The SpiderFLOAT (SF) is an offshore wind turbine substructure that promises to drastically reduce project capital expenditure via its modularized slender structure, efficient load path, and effective use of materials. The structural design of the SF must both guarantee component reliability as well as floater stability. This article discusses the theory and the analytically developed method to determine the internal loads and the required dimensions of the SF's main components during preliminary design. The classical elastic beam theory is extended to a higher order to account for buckling risk and shortening due to bending, and applied to the SF's typical leg member. Two key load cases are considered in this preliminary sizing, analyzed against both service and ultimate limit states (SLS and ULS). The first loading scenario occurs on a dry-dock during SF's assembly and is associated with the pretensioning of the cables, which realizes both the overall structure stiffness as well as the concrete leg and stem prestress. The second load case is an operational condition at sea and near turbine rated-power. After assessing the loads, the leg dimensions and the reinforcement geometry are determined by satisfying both SLS and ULS requirements based on design standards. The newly developed structural model is implemented in the software tool SOFT4S which was verified against ANSYS. The excellent agreement between the two codes proved that the computationally light SOFT4S can be reliably used in the optimization of the SF components in the context of control co-design, where both controls and structures are simultaneously designed to reduce overall costs. Graphical abstract: Source: J. Bauer (NREL) Image 1 Highlights: SOFT4S, An Innovative model for the design of the SpiderFLOAT platform for floating offshore wind turbines. 2nd order beam theory extension accounts for buckling and shortening due to bending in the main leg. Service and Ultimate Limit State design steps for the dimensioning of the SpiderFLOAT leg. Verification of the margins with respect to cable-slack conditions. Prestressing loads dominate over hydrodynamic loads.